RESOLUTION OF NON PERFORMING LOANS AT THE REPUBLIC OF INDONESIA EMPLOYEES’ COOPERATIVE (KPRI) SEGAR IN PALU CITY - Rustam, Nurul Qalbi; Oktafian, Mohamad; Luntja, Sahrul Yusman (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study maps the causes and resolution mechanisms of non-performing loans (NPLs) at the Republic of Indonesia Employees’ Cooperative (KPRI) Segar in Palu. Using a descriptive empirical legal design with a juridical–sociological approach, primary data were obtained through in-depth interviews and direct observation of management, members, and former members. Secondary data include the cooperative’s articles/bylaws (AD/ART), annual reports, loan agreements, SOPs, relevant regulations, and scholarly journals. Qualitative analysis (reduction–display–conclusion) with source triangulation was employed to assess normative compliance and field practices. Results indicate that about 18% of borrowers are delinquent, driven mainly by mismatched repayment capacity, weak loan agreements and creditworthiness assessment, negligent behavior/moral hazard, and a write-off policy lacking adequate loss reserves. The resolution mechanisms applied—direct collection, lending caps, selective collateral, and write-offs—are inconsistent, weakening the cooperative’s liquidity and resilience. Recommendations include standardizing collateral requirements across loan sizes, tightening credit assessment and administrative sanctions, establishing loss reserves/insurance support, and optimizing credit restructuring. Abstrak Penelitian ini memetakan faktor penyebab dan mekanisme penyelesaian kredit macet (NPL) pada Koperasi Pegawai Republik Indonesia (KPRI) Segar di Palu. Menggunakan desain penelitian hukum empiris deskriptif dengan pendekatan yuridis-sosiologis, data primer diperoleh melalui wawancara mendalam dan observasi terhadap pengurus, anggota dan mantan anggota. data sekunder meliputi AD/ART, laporan tahunan, perjanjian, SOP pinjaman, regulasi terkait, serta jurnal ilmiah. Analisis kualitatif (reduksi–display–kesimpulan) dengan triangulasi sumber. metode digunakan untuk menilai kepatuhan normatif dan praktik lapangan. Hasil menunjukkan sekitar 18% peminjam macet dengan pemicu utama: ketidaksesuaian kemampuan bayar, kelemahan perjanjian dan asesmen kelayakan, perilaku lalai/moral hazard, serta kebijakan write-off tanpa cadangan risiko memadai. Mekanisme penyelesaian (penagihan langsung, pembatasan plafon, jaminan selektif, write-off) belum konsisten, melemahkan likuiditas dan daya tahan koperasi. Rekomendasi mencakup standarisasi jaminan lintas plafon, pengetatan asesmen dan sanksi administratif, pembentukan cadangan kerugian/dukungan asuransi, serta optimalisasi restrukturisasi kredit.